The impact of out-of-home placement characteristics with regard to suicidal risk among adult survivors of childhood abuse. (March 2021) - Touati, Camille Danner; Miljkovitch, Raphaële; Sirparanta, Aino; Deborde, Anne-Sophie
Background: Childhood abuse is associated with increased lifetime suicidal risk (SR). Among victims of abuse, children in out-of-home care are also at risk. Out-of-home placement is aimed at stopping further exposure to maltreatment and at providing the necessary security for proper development. Research suggests that placement arrangements may impact children's mental health outcomes. Objective: The study was aimed at examining (1) the direct effects of different placement characteristics (i.e. age at first placement, number of placements, placement disruptions, total time in care, contact with biological parents, contact with siblings, placement with siblings) on SR and (2) whether these characteristics moderate the link between maltreatment and SR. Participants: The sample consisted of 77 adults (52 women; 25 men; mean age: 26.6 years) who received out-of-home care during childhood. Method: Participants completed the Childhood Trauma Questionnaire and the Mini International Neuropsychiatric Interview (for SR). Participants' records were used to determine placement characteristics and maltreatment. Results: PLS-PM analyses suggest a significant role of risk (age at first placement, number of placements, placement disruptions, contact with biological parents) and protective factors (contact with siblings, foster home placement) on SR. Risk factors also moderate the link between maltreatment and SR. Conclusions: Interventions aimed at limiting risk factors during placement seem important to reduce SR.